A Needs Assessment for a Local Social Policy Data Sharing Program - Sibbald, Shannon L.; Sedig, Kimia; Graham, Ross J.; Haji, Simoni; Chhatwal, Prabhnoor; Lizotte, Dan (Canadian Planning and Policy / Aménagement et politique au Canada)

(untitled) (Association of Canadian University Planning Programs, 2023)
Planners seek collaborative and diverse strategies to address complex challenges across Canada. In the Region of Waterloo, local governments and stakeholders adopted The Waterloo Region Community Data Program (WRCDP), a social policy data-sharing system for information on economic and social development. This study examined the needs of Community Data Program (CDP) users to investigate whether CDPs are utilized effectively. We considered how optimal use of CDP data may advance planning to resolve structural and behavioral challenges in municipalities. We surveyed 17 participants from the WRCDP to assess needs of organizational members regarding accessing data, data analysis, and networking. Participants expressed enthusiasm for the CDP’s potential but lacked training in accessing and analyzing available data. A limitation of this study is small participant sample size and how results may not be generalizable to other locations. Organizational members remained optimistic about the system’s potential for planning and policy when provided with the necessary support.